2005
DOI: 10.1080/10284150500047302
|View full text |Cite
|
Sign up to set email alerts
|

Early protein malnutrition changes learning and memory in spaced but not in condensed trials in the Morris water-maze

Abstract: Early protein malnutrition induces structural, neurochemical and functional changes in the central nervous system leading to alterations in cognitive and behavioral development of rats. The aim of the present study was to investigate the effects of protein malnutrition during lactation on acquisition and retention of spatial information using different training procedures (spaced x condensed trials). Rats treated with 16% (well-nourished) or 6% (malnourished) protein diets during the lactation phase and nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
1
11
1
7
Order By: Relevance
“…17 Spatial memory in a Morris water maze was impaired in rats after early protein malnutrition with subsequent recovery, however only when spaced trials were applied. 21 No results indicating cognitive impairment in early protein malnourished animals were found in the present study as far as working memory in the Y maze and short-term memory in a one trial OR task are concerned. These results are in line with the idea that nutritional rehabilitation may help reduce cognitive deficits.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…17 Spatial memory in a Morris water maze was impaired in rats after early protein malnutrition with subsequent recovery, however only when spaced trials were applied. 21 No results indicating cognitive impairment in early protein malnourished animals were found in the present study as far as working memory in the Y maze and short-term memory in a one trial OR task are concerned. These results are in line with the idea that nutritional rehabilitation may help reduce cognitive deficits.…”
Section: Discussioncontrasting
confidence: 71%
“…13 A range of methods have been applied to induce the nutritional deficit: temporal maternal separation, manipulation of litter size, restriction of maternal protein-energy intake, or the surgical ligation of the dam's nipples to impair lactation. [14][15][16][17] Reported effects of postnatal protein malnutrition induced by these methods in rodent offspring include changes in social, aggressive, and maternal behaviour, 18,19 exploratory behaviour and anxiety, 20 altered learning and memory capacities, 21,22 differences in the behavioural response to the administration of drugs, 23,24 and the response threshold to aversive stimuli. 16 The extent and persistence of effects of a limited period of PEM on brain development, behaviour and cognition are not entirely explored; however, they seem to be partly reversible later in life.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to changes in typical behaviors of social interaction, malnourished rats have learning difficulties in tasks that involved complex strategies or required the animal’s attention to many environmental stimuli, as shown in previous studies by our group [31,32,34,46]. …”
Section: Animal Studiesmentioning
confidence: 59%
“…Although some studies do not show significant differences in performance between well-nourished and early malnourished rats in spatial learning and memory tasks [5355]; some other studies with rats subjected to severe malnutrition in early life and/or extended until after the lactation period, covering thus the entire critical period of central nervous system development, showed that these animals take longer to learn the task and have more difficulty to retain the information learned [31,32,34,46,49,56,57]. …”
Section: Discussionmentioning
confidence: 99%
“…Early postnatal protein malnutrition affects learning (acquisition) and memory (retention) in the distal but not in the proximal cue version of the Morris water maze and changes learning and memory in spaced but not in condensed trials in the same test (Fukuda et al 2002;Valadares and Almeida 2005).…”
Section: Discussionmentioning
confidence: 99%